Analysis of the Effect of Capital Structure, Profitability, and Liquidity, on the Value of Property and Real Estate Companies Listed on the Indonesia Stock Exchange (2019-2023) - Fadin, Adnan Fadin; Mulyati; Ramadhan, Rizky (Jurnal Economic Resource, 2025)
The property and real estate sectors play an important role in supporting a country's economic growth. In Indonesia, this sector shows dynamic development and tends to fluctuate but continues to move forward. The 2019 to 2023 timeframe includes a number of significant events, including the COVID-19 pandemic that had a significant impact on various sectors, including property and real estate. This study aims to empirically examine the influence of capital structure, profitability, and liquidity on company value in issuers in the Property and Real Estate sector listed on the Indonesia Stock Exchange during the period. The method used in this study is a quantitative approach, with a population of 92 companies based on IDX Statistics 2023 data. The sampling technique was carried out purposively, resulting in 58 companies that met the criteria, and multiplied by the 5-year observation period, a total of 290 panel data observations were obtained. Data processing is carried out with the help of EViews software version 13. The results of the t-test showed that the variables of capital structure, profitability, and liquidity did not have a statistically significant influence on the company's value. Furthermore, the results of the F test also showed that simultaneously the three variables did not have a significant influence on the value of companies in the property and real estate sectors during the 2019-2023 period.